Assessment of Anti-Müllerian Hormone Level in Management of Adolescents with Polycystic Ovary Syndrome - Dursun, Fatma (J Clin Res Pediatr Endocrinol, 2016)
OBJECTIVE: This study was oriented to investigate the benefit of anti-Müllerian hormone (AMH) level in the management of polycystic ovary syndrome (PCOS). To assess the impact of metformin and oral contraceptives (OC) on serum AMH levels in a cohort of adolescents with PCOS. METHODS: Forty-nine adolescents with PCOS were recruited to the study. Twenty-nine patients without insulin resistance were treated with OC (group 1), and 20 patients with insulin resistance were treated with metformin and OC (group 2). AMH and androgen levels were measured prior to and 6 months after the initiation of treatment. RESULTS: AMH levels were significantly decreased with treatment in both group 1 (p=0.006) and group 2 (p=0.0048). There was a significant correlation between pre- and post-treatment AMH and left ovarian volume (pretreatment: rho=0.336, p=0.018; post-treatment: rho=0.310, p=0.034). CONCLUSION: This study investigated two different treatment regimens in adolescents with PCOS and revealed that AMH levels decreased with treatment. AMH levels were correlated with ovarian volume.